Ronald Lamola’s ICJ Discursive Construction of Israel-Palestine Conflict - Apriliani, Putri Salsabilah; Arifin, M. Bahri (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
This research aimed to reveal Ronald Lamola’s discursive construction at the International Court of Justice (ICJ) due to the Israel-Palestine conflict. As the Minister of International Relations and Cooperation of South Africa, Ronald Lamola represented South Africa to deliver opening remarks before providing its claims and supporting evidence to the court. In this research, the researcher revealed how Ronald Lamola constructed his identity as the Minister of International Relations and Cooperation of South Africa, and how he positioned himself in the Israel-Palestine conflict through his speech at the ICJ. The researcher used qualitative descriptive methods as the methodology for the data displayed. The data was analyzed using the five discursive strategies proposed by Reisigl and Wodak (2009), which were the nomination, predication, argumentation, perspectivization, and mitigation and intensification. As a result, the researcher finds that Ronald Lamola’s opening remarks were constructed with these five discursive strategies, which were dominated by the use of the nomination strategy, that shaped his audience’s perception of the actors and situation referred. The overall findings not only showed his identity and position as the Minister of International Relations and Cooperation of South Africa, but also as a member of the United Nations (UN). The findings of this research were expected to contribute to the Discourse Historical Approach (DHA) field by providing insights into the use of discursive strategies in national identity, political ideology, and international law discursively throughout certain situations.